EVALUATION OF EDUCATIONAL ACHIEVEMENTS OF STUDENTS OF TECHNICAL UNIVERSITIES AS PEDAGOGICAL PROBLEM - Захарченко, Надія Миколївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article, going of scientists is generalized near interpretation of concepts «evaluation», «educational achievements»; expediency of realization of new strategies of development of education is reasonable in Ukraine in the educational process of technical educational establishments, in particular in the process of evaluation of educational achievements of students. The author accents that practical achievement in the evaluation of educational achievements of students in the educational process of higher technical initial establishments